UPAYA MENYELAMATKAN MASYARAKAT DARI PENYAKIT HEPATITIS AKIBAT HIV MELALUI PELATIHAN KADER KESEHATAN - Sensusiati, Anggraini; Rachman, Brian Eka (Universitas Negeri Surabaya, 2025)
Hepatitis co-infection in HIV patients is a significant health problem due to the similar route of transmission and the resulting impact on liver health. Hepatitis B and C virus co-infection is common among HIV-infected people in Indonesia. Hepatitis co-infection in HIV patients can lead to more severe liver disease and increased mortality. The working area of Puskesmas Mulyorejo is an area with a high number of migrants, considering that many large housing estates and universities are scattered in the area. Therefore, it is important to educate the community to increase their knowledge and understanding of Hepatitis infection in HIV patients, so that the incidence of this disease can be reduced. The activity method is carried out in the form of education and training for health cadres with the hope that they can improve their ability to provide education to the community. A total of 38 health cadres and 7 people from the Surabaya HIV Care community participated in this education and training. The results showed that 41 people (91.1%) had increased knowledge and ability to carry out education, with a percentage increase in knowledge of 25.89%.